Gypsum amendment influences soil and plant chemical composition temporarily - Yli-Halla, Markku; Taskinen, Antti; Ekholm, Petri (Agricultural and Food Science, 2023)
Field application of gypsum (CaSO4 × 2H2O) is a tool to decrease phosphorus (P) load to watercourses. Effects of gypsum application (4 tons ha-1) on soil and crop composition were monitored up to four years after the treatment in the Savijoki catchment, southwestern Finland. Eleven amended fields and 17 control fields were analyzed for easily soluble P, Ca, Mg, K, S, pH(H2O), electrical conductivity (EC) and loss-on-ignition. Plant samples were analyzed for most nutrients and Se. Downward S transport was monitored in two fields. In the first spring after gypsum application, but not later, S concentrations and EC were substantially but not harmfully elevated in the plough layer, with no other significant effects on soil composition. Sulfur leached out slightly less rapidly from clay than from the coarse mineral soil. Plant S concentration increased for the first and the second year. In conclusion, gypsum application did not have adverse effects on soil or crop chemical composition in this survey of predominantly clay soils.